The Development of Ecotourism Model at Natural Attractions of Tete Batu Village in East Lombok - Nofiarli, Nofiarli (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
Tourist village of Tete Batu is located at Sikur District in East Lombok Regency, Nusa Tenggara Barat Province. With its scenic beauty along the southern foot of Rinjani Mountain and its green, natural, beautiful and mild countryside atmosphere, Tete Batu Village offers economic potential to its community. Tourism sector needs a good tourism development that can develop existing potential with a maximum result. This research was aimed to find the effect of natural attraction development in Tete Batu Village that adopted Ecotourism Model in the interest of increasing the number of tourist arrivals. Technique of data analysis being used was SWOT analysis with qualitative approach. There were two types of data that were collected, namely primary and secondary data. Primary data was obtained through field observation, interview and questionnaire, while secondary data was collected from related literature study. The result showed that natural attractions in Tete Batu village could be developed by using Ecotourism model because its condition could attract tourists and the management was done by the society and based on local nature and culture.